Performance analysis of men's K-1 1000 meter sprint at the 99th National Sports Festival - Sohn, J.-H. (Journal of Digital Convergence, 2019)
This study was conducted to analyze the lap time of the K-1 1000m final race of men's general division and to develop strategies to adjust the pace for the intervals to improve the performance. We measured the lap time of the final race of the 99 th National Sports Festival by 250m intervals and compared them with the data of the World Championship finals held in 2018. The final average record of domestic top-ranked players was 248.651 seconds, and the top international's 210.826 seconds. There was a time gap of 38 seconds in the record. In lap-time, it was 8, 11, 6, and 13 seconds behind every 250m. World Championship players used the Fast-Maintain-Maintain-Spurt strategy while domestic players used the pacing strategy of Fast-Slow-Fast-Slow. In order to improve the performance of domestic players, it is necessary to adjust overall pace control strategies to maintain the pace after the quick start and to spurt at the last lap.